Does technical education improve academic outcomes? Evidence from Brazil - Gregory Elacqua; Patricia Navarro-Palau; Maria Fernanda Prada; Sammara Soares (Inter-American Development Bank (IDB), 2019)
Despite the renewed interest in technical education, only a handful of studies analyze its effect on academic outcomes. In this paper we apply a regression discontinuity design to oversubscribed technical high school tracks in Pernambuco, Brazil, to identify the impact of technical education during high school on student academic outcomes. We find that students above the technical high school admission exam score cutoff drop out less from high school and have Math and Portuguese standardized test scores over 0.1 standard deviations higher than students below the cutoff. We also find that students above the cutoff were more likely to attend schools offering a longer school day and better school, teacher, and peer characteristics. Comparing technical high schools with academic schools with similar characteristics, we find no differences in terms of achievement but significantly lower dropout rates. This evidence suggests that the estimated effect of having the opportunity to enroll in technical high schools on student achievement may be driven by the school characteristics while the nature of the instructional content seems to be effective in reducing dropout rates during high school.
Keywords: I21; J24; 330; Education; technical education; high school; Latin America; Brazil